Chilli Spores from Mycorrhizal Endogone Species and Soil Chemical Analysis - Kanaujiya, Yashika; Agnihotri, Amita (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
VAM fungi have received considerable attention in recent years with regard considerable attention in recent years with regard to nutrition and development of host plants. VAM root colonization is the results of the interaction between the host soil and fungus. This study clearly brings out the influence of soil type on VAM development, i.e. the red soil type was found to be superior to the black clayey soil.